Analisis Pengaruh Belanja Pemerintah Hijau terhadap Pencapaian SDGs di Indonesia Tahun 2020–2025 - Farizan, Muhammad Irsyad; Ramadhan, Gilang; Alhakim, Burhanuddin; Permatasari, Rosita Ayu (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Sustainable development has become a key agenda in global and national development policies, particularly since the adoption of the Sustainable Development Goals (SDGs). In the Indonesian context, green fiscal policy is viewed as a strategic instrument to promote the achievement of the SDGs through budget allocations oriented toward environmentalsustainability. This study aims to analyze the effect of green government spending in the renewable energy sector on the achievement of the SDGs in Indonesia during the 2020–2025 period. The study uses a quantitative approach with anexplanatory research approach. The data used are secondary data sourced from the Ministry of Finance of the Republic ofIndonesia, the SDGs Index (UNDP), and the Central Statistics Agency (BPS). The analytical method used is panel data regression with a Fixed Effect Model (FEM) approach to control for differences in characteristics between provinces. The descriptive analysis results show that Indonesia's green budget allocation has consistently increased during the studyperiod, accompanied by a shift in sectoral priorities from a dominant transportation sector to strengthening the energy and buildings sectors. These findings indicate a strengthening government commitment to promoting a green economy transitionand achieving sustainable development goals, particularly in the areas of clean energy and climate action. However, the effectiveness of green government spending in improving SDG achievement is still heavily influenced by the quality of policy implementation, institutional capacity, and macroeconomic conditions. This research is expected to provide an empirical contribution to the development of green fiscal policy literature and serve as a consideration in formulating sustainable development policies in Indonesia.